Combined hydrogen and ethanol production from sugars and lignocellulosic biomass by Thermoanaerobacterium AK54, isolated from hot spring - Sigurbjornsdottir, Margret Audur; Orlygsson, Johann
Combined biohydrogen and bioethanol (CHE) production from monosugars, polymeric carbohydrates and hydrolysates made from various lignocellulosic biomasses was investigated by strain AK54, a saccharolytic, thermophilic ethanol and hydrogen producing bacterium isolated from a hot spring in Iceland. Optimum growth conditions for the strain were between pH 5.0–6.0 and at 65°C. As determined by full 16S rRNA analysis, strain AK54 belongs to the genus Thermoanaerobacterium, most closely affiliated with Thermoanaerobacterium aciditolerans (99.0%). Effect of increased initial glucose concentration on growth and end product formation was investigated and good correlations were observed between increased substrate loadings and end product formation of up to 50mM where clear inhibition was shown. The ability to utilize various carbon substrates was tested with positive growth on xylose, glucose, fructose, mannose, galactose, sucrose and lactose. The major end products in all cases were ethanol, acetate, lactate, hydrogen and carbon dioxide. By lowering the partial pressure of hydrogen during glucose degradation, the end product formation was directed towards hydrogen, acetate and ethanol but away from lactate. Hydrogen and ethanol production from hydrolysates from biomass (7.5gL−1 (dw)); cellulose, newspaper, grass (Phleum pratense), barley straw (Hordeum vulgare), and hemp (Cannabis sativa L), was investigated. The biomass was chemically (acid/alkali) and enzymatically pretreated. The highest ethanol production was observed from cellulose hydrolysates (24.2mM) but less was produced from lignocellulosic biomasses. Chemical pretreatment of biomass hydrolysates increased hydrogen and ethanol yields substantially from barley straw, hemp and grass but not from cellulose or newspaper. The highest hydrogen was also produced from cellulose hydrolysates or 6.7mol-H2g−1 TS pretreated with alkali (12.2mol-H2g−1 glucose equivalents) but of the lignocellulosic biomass, highest yields were from grass pretreated with base (4.9mol-H2g−1 ...